Diferensiasi Produk, Eco-label, Dan Brand Awareness Sebagai Peran Pengambilan Keputusan Pembelian Pada Produk Eiger - Ayes, Yoki Taufiqul; Hariyadi, Guruh Taufan; Yovita, Lenni; Putra, Febrianur Ibnu Fitroh Sukono (Politeknik Negeri Ambon, 2024)
The era of dynamic globalization and rapid technological progress has had an impact on the economy, resulting in very tight business competition. One of them is the increase in companies adopting innovation by making environmentally friendly products. This research aims to analyze the influence of product differentiation, eco-labels, and brand awareness on purchasing decisions for Eiger products in Semarang City. The population and sample of this research was carried out using a purposive sampling technique on an unknown number of consumers of Eiger products. This study used a sample based on the formula N = (8 × number of indicators) = 8 × 19 = 152 respondents. The research method applied is a quantitative approach and multiple linear regression analysis which is used to test the hypothesis using the SPSS 26 application. The research results imply that product differentiation, eco-label and brand awareness variables have a positive and significant effect on purchasing decisions for Eiger products in Semarang City. Keywords: Product Differentiation; Eco-label; Brand Awareness; Buying decision; Eiger